1993
DOI: 10.1159/000168661
|View full text |Cite
|
Sign up to set email alerts
|

Urinary N-Acetyl-Glucosaminidase Excretion and Environmental Lead Exposure

Abstract: To understand the relationship between chronic low-level lead exposure and renal function, residents living nearby a lead battery factory for more than 10 years were selected and entered in this cross-section study. The residents living in the 1 st village, within 500 m from the factory, were grouped in group 1; those in the 2nd village, within 1,000-1,500 m, in group 2, and those in the 3rd village, far from any lead-contaminated sources, in group 3. Twenty-four-hour urinary N-acetyl-glucosaminidase (NAG) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 16 publications
(24 reference statements)
3
25
0
Order By: Relevance
“…Those are in agreement with previous investigations done by Lin et al (1993) and Abo El-Magd et al (2015). Interstitial, tubular and glomerular damage are also characteristic renal lesions due to lead acetate toxicity.…”
Section: Advances In Animal and Veterinary Sciencessupporting
confidence: 94%
“…Those are in agreement with previous investigations done by Lin et al (1993) and Abo El-Magd et al (2015). Interstitial, tubular and glomerular damage are also characteristic renal lesions due to lead acetate toxicity.…”
Section: Advances In Animal and Veterinary Sciencessupporting
confidence: 94%
“…Tests for Detection (74,(135)(136)(137)(138)(139)(140). Verschoor et al (59), in a study of lead workers with blood lead levels below 60 pg/dl (2.89 pmol/l), found the excretion of NAG to be the most sensitive marker of renal tubular dysfunction.…”
Section: Lead Nephropathymentioning
confidence: 99%
“…(8,9) They also showed that long-term, low-level environmental lead exposure may be associated with renal tubular and glomerular damage in patients with immunoglobulin A nephropathy (22) and in residents who had been living near a lead battery factory for more than ten years. (23) The findings of these studies suggest that there may be a positive association between long-term lead exposure (resulting in a high body burden of lead) and impaired kidney function.…”
Section: Discussionmentioning
confidence: 93%